Information disclosure in global energy governance - FLORINI, Ann (Institutional Knowledge at Singapore Management University, 2011)
The lack of global consensus on how to deal with complex energy governance challenges has led to the emergence of information disclosure initiatives as governance tools in and of themselves. This article assesses the effectiveness of disclosure mechanisms as tools of energy governance by looking at the motivations and desired outcomes behind a series of disclosure-based initiatives in the energy sector, namely: making energy markets work more efficiently; inducing corporations to internalize their climate change externalities; and improving democratic processes that lead to better energy governance outcomes. The disclosure initiatives assessed in this article adopt different strategies to achieve their objectives, mobilizing either users of information or holders of information, with varying effectiveness. Where pressures for secrecy exist, voluntary disclosures without formal sanctions to incentivize compliance have limited impact. Where users of information are primarily mobilized as drivers of change, the disclosures have to be easily understood to have impact; this is no easy task when it comes to the energy sector. Disclosure mechanisms that use a strategy of engagement and building of wide networks have perhaps the best potential to influence (or pressure) holders of information to change their behavior accordingly. However,disclosure mechanisms underpinned by western-influenced values of governmental transparency may not be as effective in countries that lack democratic systems.